BCG vaccination induces enhanced humoral responses in elderly individuals. (March 2023) - Kumar, Nathella Pavan; Padmapriyadarsini, Chandrasekaran; Rajamanickam, Anuradha; Bhavani, Perumal Kannabiran; Nancy, Arul; Jeyadeepa, B.; Renji, Rachel Mariam; Babu, Subash
Abstract: Background: Studies have reported the beneficial effects of Bacillus Calmette Guerin (BCG) vaccination, including non-specific cross-protection against other infectious diseases. Methods: We investigated the impact of BCG vaccination on the frequencies of B cell subsets as well as total antibody levels in healthy elderly individuals at one month post vaccination. We also compared the above-mentioned parameters in post-vaccinated individuals to unvaccinated controls. Results: Our results demonstrate that BCG vaccination induced enhanced frequencies of immature, classical and activated memory B cells and plasma cells and diminished frequencies of naïve and atypical memory B cells. BCG vaccination induced significantly increased levels of total IgG subclass isotypes compared to baseline. Similarly, all of the above parameters were significantly higher in vaccinated individuals compared to unvaccinated controls. Conclusion: BCG vaccination was associated with enhanced B cell subsets, suggesting its potential utility by enhancing heterologous immunity.